Deuteronomy Reads the Pentateuch - Baden, Joel S. 1977- (2020)
The parallel narratives in Deuteronomy and in Exodus-Numbers have long provided a basis for literary-historical investigations of the composition of the Pentateuch. They also, however, contribute significantly to a canonical reading of Deuteronomy and its place in the Pentateuch. The parallel stories - and specifically the differences between them - allow for a sharper definition of Deuteronomy's message, the character of Moses, and the nature of biblical interpretation.
Keywords: Moses; Deuteronomy; Exodus; Numbers; Pentateuch